The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022 IEEE PES Innovative Smart Grid Technologies Conference Europe (ISGT-Europe) 2022
DOI: 10.1109/isgt-europe54678.2022.9960381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of short-circuit ratio as a system strength indicator in converter-dominated power systems

Abstract: This paper investigates the applicability of shortcircuit ratio (SCR) as a system strength indicator in power systems with a high penetration of voltage source converters (VSCs). In power systems dominated by synchronous generators, the SCR has been widely used to estimate the system strength by using short-circuit level information obtained at the relevant bus. However, the emerging converter technology such as VSCs has different short-circuit characteristics from synchronous generators, in the sense that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…According to (9), reducing the d x value can increase the SCR N at the point of interconnection. From figure 5 (a), it can be observed that under the same fault conditions, a larger SCR N results in a smaller voltage drop and a smaller transient overvoltage, indicating a positive correlation between voltage support strength and the SCR N .According to (5), changing the d x value does not affect the magnitude of the conventional SCR.…”
Section: Validation Of the Short-circuit Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…According to (9), reducing the d x value can increase the SCR N at the point of interconnection. From figure 5 (a), it can be observed that under the same fault conditions, a larger SCR N results in a smaller voltage drop and a smaller transient overvoltage, indicating a positive correlation between voltage support strength and the SCR N .According to (5), changing the d x value does not affect the magnitude of the conventional SCR.…”
Section: Validation Of the Short-circuit Ratiomentioning
confidence: 99%
“…The short circuit ratio (SCR) is one of the important indicators for assessing the voltage support capability of new energy grid integration systems [6][7][8]. Traditional SCR calculations neglect the contribution of new energy sources to the system's short circuit capacity [9]. The calculation of the SCR becomes incomplete when considering the reactive power voltage regulation capability of new energy power plants.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it guarantees that the power flow P ijc on that line remains fixed at zero when the line is withdrawn. The upper and lower bounds of the unit active output are shown in Formula (17). The bus voltage phase angle difference constraint upper and lower limitations are given in Formula (18) when the line is operational.…”
Section: Power Flow Constraintsmentioning
confidence: 99%
“…To limit SCC while ensuring sufficient system strength support for the DC system, it is necessary to express system strength constraints analytically. In engineering applications and theoretical research, the short‐circuit ratio (SCR) index is typically used to characterise the relative strength of the AC and DC systems [16, 17]. Considering the interaction of various DC converter stations in a multi‐infeed DC receiving‐end system, the CIGRE DC Working Group has defined the multi‐infeed short‐circuit ratio (MISCR) [18].…”
Section: Introductionmentioning
confidence: 99%